52.5k views
2 votes
-2(4x+3)-(x-7)=46 solve please step by step

User Uotonyh
by
5.0k points

2 Answers

1 vote

Answer:x = - 5

Step-by-step explanation:

Fist distribute the -2(4x+3) - (x-7)

-8x -6 - (x - 7) next, get rid of the parenthesis by distributing the -1

-8x-6+( -x+7)=46

combine like terms -8-x= -9x

-6+7=1

write in order-9x+1=46

-9x+1-1=46-1

-9x=45

divide both sides by -9

x= -5

User Cameron Aavik
by
5.0k points
5 votes

Answer:

x=−5

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

−2(4x+3)−(x−7)=46

−2(4x+3)+−1(x−7)=46(Distribute the Negative Sign)

−2(4x+3)+−1x+(−1)(−7)=46

−2(4x+3)+−x+7=46

(−2)(4x)+(−2)(3)+−x+7=46(Distribute)

−8x+−6+−x+7=46

(−8x+−x)+(−6+7)=46(Combine Like Terms)

−9x+1=46

−9x+1=46

Step 2: Subtract 1 from both sides.

−9x+1−1=46−1

−9x=45

Step 3: Divide both sides by -9.

−9x

−9

=

45

−9

x=−5

User Willower
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.